Who Arrests those Accused by the ICC?. (30th July 2018) - Fulford, Adrian
Abstract : In a world in which war crimes, crimes against humanity, and genocide are not uncommon, the institution that was set up to have jurisdiction over them is in danger of being unable to discharge its mandate. Put starkly, the International Criminal Court (ICC) suffers too frequently from an inability to arrest or otherwise detain alleged perpetrators, whether the prosecutor is acting proprio motu or is following a reference to the court by a state party or the Security Council. The situation of Saif al-Islam Gaddafi is a case in point: notwithstanding the Security Council's referral of Libya to the ICC, at least as a member of the public it is difficult to detect any substantial international pressure that has been applied to have Gaddafi transferred to the Court; instead, he has been mooted as a candidate in future presidential elections. In total, the Court has issued thirty-two arrest warrants and nine summonses to appear, yet has held only nine individuals in custody, with fifteen still at large. The fugitives include citizens of the Democratic Republic of Congo, Uganda, Sudan, Kenya, Libya, and the Ivory Coast. Once the present trials before the court have concluded, there is only one case potentially waiting in the wings. A sole outstanding individual, Al-Hassan Ag Abdoul Aziz Ag Mohamed Ag Mahmoud from Mali, has made an initial appearance, and later this year the pre-trial stage of his case should commence; otherwise, there are simply the three trials in progress. However, I urge careful reflection before the Court is blamed for periods in which its docket of cases is lean.